Are the International Parkinson disease and Movement Disorder Society progressive supranuclear palsy (IPMDS-PSP) diagnostic criteria accurate enough to differentiate common PSP phenotypes?. (December 2019) - Shoeibi, Ali; Litvan, Irene; Juncos, Jorge L.; Bordelon, Yvette; Riley, David; Standaert, David; Reich, Stephen G.; Shprecher, David; Hall, Deborah; Marras, Connie; Kluger, Benzi; Olfati, Nahid; et al.
Abstract: The International Parkinson Disease and Movement Disorder Society PSP study group (IPMDS-PSP) recently published new clinical diagnostic criteria for progressive supranuclear palsy (PSP). Currently, there is no data regarding the accuracy of these sets of criteria for differentiating various PSP phenotypes. We discuss the accuracy of the IPMDS-PSP criteria for differentiation of patients with the PSP- Richardson phenotype (PSP-RS) from those with the PSP-Parkinsonism (PSP-P) using data from a sample of 274 clinically diagnosed PSP patients participating in the Environmental Genetic PSP (ENGENE-PSP) case control study. Using National Institute of Neurological Disorders and Stroke and the Society for PSP (NINDS-SPSP) criteria and the Williams criteria we categorized 259 of these patients as probable PSP-RS and 15 as PSP-P. The IPD-MDS PSP-RS and PSP-P criteria were unable to distinguish the PSP-RS from the PSP-P phenotypes in this sample. Nearly all (92.6%; 240 out of 259) the PSP-RS patients and over half (60%; 9 out of 15) of the PSP-P patients fulfilled both the IPMDS criteria for PSP-RS and PSP-P. Applying the newly proposed multiple allocation extinction rules decreased the number of overlapping diagnoses among the NINDS-SPSP PSP-RS patients, however problems remained in the PSP-P group. Diagnostic accuracy might be improved by modification of timelines for development of falls and other parkinsonian features. Highlights: It is critical to differentiate between PSP phenotypes for prognostication and patient inclusion in trials . Using the IPMDS-PSP criteria a significant proportion of PSP patients could be classified both as PSP-RS and PSP-P . This will limit the usefulness of these criteria to differentiate between the more benign and progressive phenotypes. Use of multiple allocation extinction rules partially improves diagnostic accuracy of the IPMDS-PSP criteria. Further refinement of the IPMDS-PSP criteria is needed.